Life Cycle Assessment (LCA) Analysis Operational Vehicles Telecommunication Industry at PT. X in East Java Using OpenLCA Software and the ReCipe Midpoint H Method - Darmawan, Agges Brian; Jawwad, Muhammad Abdus Salam (UPN Veteran Jatim, 2025)
The telecommunications industry heavily relies on operational vehicles to support network maintenance and customer service activities. This study aims to analyze the environmental impact resulting from the emissions of operational vehicles at PT. X, focusing on the East Java operational region. A Life Cycle Assessment (LCA) was conducted in accordance with ISO 14040, emphasizing the vehicle use phase. Primary data includes gasoline consumption and a total distance during the 2024 operational year. The analysis was performed using OpenLCA software with the Ecoinvent 3.3 database and the ReCipe Midpoint (H) method to quantify emissions and their associated environmental impacts. Results indicate that carbon dioxide (CO₂), carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOₓ), sulfur dioxide (SO₂), and particulate matter (PM10) are the primary contributors to environmental impact categories such as climate change, marine eutrophication, particulate matter formation, photochemical oxidant formation, and terrestrial acidification. The findings provide a quantitative basis for evaluating the environmental burden of operational fleets and highlight the importance of implementing efficient fleet management, eco-driving practices, and integrated emission reduction policies as part of corporate sustainability strategies.